What drives the purchasing of foods with high sugar? Evidence from Turkey. Issue 5 (25th April 2019) - Sürmeli, Gökhan; Elshiewy, Ossama; Ülengin, Burç
Abstract : Purpose: The purpose of this paper is to examine how the share of expenditure on foods with high sugar is influenced by purchasing behaviour and household characteristics in Turkey. Design/methodology/approach: Food purchases of a large representative sample of Turkish households ( n =10, 682) were observed over a two-year time span. A linear mixed effects model is estimated to analyse the drivers of households' share of expenditure on foods with high sugar in a longitudinal setting. Findings: Lower shopping frequency, larger shopping baskets, more promotional purchasing and higher usage of modern retail formats lead to a higher share of expenditure on foods with high sugar. This share decreases with higher income and education. Households living in urban areas have lower expenditure on foods with high sugar. Households in the Aegean and Mediterranean regions show the highest share of expenditure on foods with high sugar across Turkey. Children within the household lead to a higher share of expenditure on foods with high sugar whereas this share decreases with increasing household size and being in later stages of life. Originality/value: Analysing household panel data provides a more realistic perspective of longitudinal food purchasing behaviour compared to studies using cross-sectional designs. Furthermore, this large-scale study in Turkey provides valuable insights for health researchers and policymakers to improve public health due to being conducted in a newly industrialised country with high rates of obesity and type 2 diabetes, a fragmented retail environment and diverse geographical regions.